Some non-intellective and intellective factors and their relationship to academic achievement of U.P. College of Agriculture freshmen - Lozada, Rhodelia Buenaventura 1941- (s.n.], 1966)
This is a comparison of the three groups of college freshmen who differed widely in their reactions to the demands of college life as measured by the level of first year academic achievement. The three groups are compared with respect to: non-intellective factors (educational attainment of parents, economic index, type of school from which they graduated, etc.) and intellective factors (scholastic aptitude scores of the College Freshman Examination and high school achievement)